The effect of the guided inquiry learning model on student's learning outcomes in fractional materials in fifth grade elementary school - Muhadi, Muhadi; Utaminingsih, Sri; Rismiyanto, Rismiyanto (Universitas Negeri Yogyakarta, 2022)
Students' mathematical abilities will only become material that follows a series of procedures without knowing its meaning if students' reasoning abilities are not developed. The purpose of the study was to determine the effect of the Guided Inquiry learning model on student learning outcomes on fraction material in grade V Elementary School. This type of research uses a quantitative approach. The design uses a quasi-experimental design with an equivalent control group design. The sample consists of 2 groups, namely group 1 using conventional learning, group 2 using the Guided inquiry model. The research instrument was in the form of test scores (pre-test scores and post-test scores). Data analysis techniques in the form of normality test, homogeneity test, t-test. The results showed that there was an influence of the Guided Inquiry learning model on the student learning outcomes of fractions in grade V Elementary School with an average of 74.84%.